Peran Guru dalam Pengimplementasian Teks Persuasi di Sekolah Dasar Negeri Cisoka III - Dari, Suci Ulan; Julianto, Indra Rasyid (Cahaya Smart Nusantara, 2025)
This research examines various efforts to improve persuasive text writing skills in elementary school students. Some of the studies discussed show that although most students have understood the basic structure of persuasive texts, many of them require further assistance to achieve optimal writing skills. The approaches used include more structured learning methods such as planned writing exercises, teacher-student feedback, and the use of innovative media. Learning models such as media were able to improve students' understanding and skills in writing persuasive texts. The research methods used in these various studies include descriptive qualitative research, literature study and direct interviews to find out the learning methods towards improving students' writing skills. The results showed that the application of these models can improve students' persuasive writing skills by providing a deeper understanding by giving assignments to students.